Melatonin reduces nanoplastic uptake, translocation, and toxicity in wheat. Issue 3 (26th August 2021) - Li, Shuxin; Guo, Junhong; Wang, Tianya; Gong, Lei; Liu, Fulai; Brestic, Marian; Liu, Shengqun; Song, Fengbin; Li, Xiangnan
Abstract: With increasing plastic production and consumption, large amounts of polystyrene nanoplastics are accumulated in soil due to improper disposal causing pollution and deleterious effects to environment. However, little information is available about how to alleviate the adverse impacts of nanoplastics on crops. In this study, the involvement of melatonin in modulating nanoplastic uptake, translocation, and toxicity in wheat plant was investigated. The results demonstrated that exogenous melatonin application reduced the nanoplastic uptake by roots and their translocation to shoots via regulating the expression of genes associated with aquaporin, including the upregulation of the TIP2‐9, PIP2, PIP3, and PIP1.2 in leaves and TIP2‐9, PIP1‐5, PIP2, and PIP1.2 in roots. Melatonin activated the ROS scavenging system to maintain a better redox homeostasis and ameliorated the negative effects of nanoplastics on carbohydrate metabolism, hence ameliorated the plant growth and enhanced the tolerance to nanoplastics toxicity. This process was closely related to the exogenous melatonin application induced melatonin accumulation in leave. These results suggest that melatonin could alleviate the adverse effects of nanoplastics on wheat, and exogenous melatonin application might be used as a promising management strategy to sustain crop production in the nanoplastic‐polluted soils.